A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae) - Murányi, Dávid; Vinçon, Gilles (Zootaxa, 2017)
In the recent annotated catalogue of the Turkish Plecoptera, the fauna of Anatolia are considered remarkably rich with 32 micro-endemic species currently recorded (Darilmaz et al. 2016). The major hot spot is the Pontus, the eastern Black Sea region of Turkey. Nearly half of these micro-endemic stonefly species are only known from this region. The eastern subregion of the Pontus has a direct connection with the Caucasian stonefly fauna. This subregion even has an endemic species group of Leuctra Stephens, 1836, presently including four known species (Vinçon & Sivec 2001).